New insights on the 2012–2013 uplift episode at Fernandina Volcano (Galápagos). Issue 2 (2nd August 2017) - Pepe, S.; Castaldo, R.; De Novellis, V.; D'Auria, L.; De Luca, C.; Casu, F.; Sansosti, E.; Tizzani, P.
Abstract: We analysed the 2012–2013 uplift episode at Fernandina Volcano (Galápagos) through the inverse modeling of Differential Synthetic Aperture Radar Interferometry (DInSAR) ground displacement field. The post-processing analysis of COSMO-SkyMed satellite data revealed that the uplift phenomenon can be divided in three distinctive intervals in which the displacement maintains a nearly constant deformation rate. We used both ascending and descending acquisitions to evaluate the vertical and the horizontal E–W components of the displacement field. The vertical displacement is strongly limited in a narrow region around the caldera rim, where the circumferential fissures that border the summit platform are localized and the E–W component of the horizontal displacement affects the external volcano flanks, up to the apron region. Moreover, we exploited the DInSAR time-series by performing a cross-correlation analysis: both vertical and E–W cross-correlated maps confirm that the observed uplift episode is related to the existence of a single active source, approximated as a pipe-like source. Indeed, our results, obtained through an inverse modeling approach by investigating different type of analytic sources, suggest the existence of an over pressurized pipe-like source, with a slight dip toward SE and located beneath the summit caldera region. The modeled geodetic source could represent the shallower part of an extended and deeper magmatic reservoir.